Strategi Pendidikan Anti Korupsi dalam Menghadapi Krisis Integritas Generasi Muda - Devy, Azizah Aisyah (Maliki Interdisciplinary Journal, 2026)
Corruption is a systemic issue that hinders national development and undermines social integrity. The younger generation, as the nation’s successor, faces an integrity crisis reflected in academic dishonesty, plagiarism, and tolerance of unethical behavior. Anti-corruption education emerges as a preventive strategy to instill values of honesty, responsibility, discipline, and justice through both formal and informal learning processes. This article emphasizes the importance of collaboration among schools, families, communities, and state institutions in fostering an anti-corruption culture. Effective strategies include integrating anti-corruption values into curricula, role modeling by educators, participatory approaches such as seminars and honesty canteens, and the use of digital literacy to expand educational reach. Anti-corruption education not only builds knowledge but also shapes character and moral awareness across generations. With Indonesia’s demographic bonus, the younger generation holds a strategic role as agents of change toward a society built on integrity and free from corruption.